Energy harvesting system based on road pavement incorporated with thermoelectric generator system - Sharuddin, Muhammad Syadza (2021)
Thermal energy harvesting (TEH) is an exciting subject due to its advantage of being easily procured, whether from natural sources or waste heat. Asphalt road is one of the examples of waste heat sources that can be easily collected due to its availability almost everywhere on earth. A thermoelectric generator (TEG), which operates based on the Seebeck effect, can be utilized to harvest thermal energy from the road. The Seebeck effect produces potential differences when there is a temperature gradient between two dissimilar electrical conductors. This research aims to develop an energy harvesting system on road pavement using TEG device. An energy management system is also designed and analyzed for the road thermal energy harvesting system. The improvement of the system is evaluated based on behavior and characteristic of the temperature difference across the TEG surface, output voltage, and efficiency. Experiments were performed on pavement samples installed with aluminium and copper plates under three different conditions. Firstly, the experimental result shows that the best type of metal plate is copper plate. Secondly, increasing the number and length of metal plates can produce a higher yield. Thirdly, the TEG’s thermal connection test indicated that stacking TEG on top of each other (2x2 and 1x4) increases the output voltage and efficiency. The best cooling method is water tank cooling, where it generates the highest temperature gradient and output voltage compared to ambient and heatsink cooling. The energy management experiment results presented that DC1587A can charge supercapacitors faster than ECT310 because DC1587A has MPPT (maximum power point tracking) capability. TEH from asphalt pavement is green, sustainable, and at less cost. The potential of this technology is very promising and it can help supply extra energy from excess heat anywhere.